Ruminative Response Styles and Metacognitions in Internet Addicts - Omer SENORMANCI; Ramazan KONKAN; Oya GUCLU; Guliz SENORMANCI (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: Although cognitive behavioral model of Internet addiction has been well described, studies on metacognitions and ruminative response styles related with Internet addiction are very limited. The aim of the present study was to compare metacognitions and ruminative response style in Internet addicts with a healthy control group. Method: The study included 30 males who presented to our Internet Addiction Outpatient clinic, and diagnosed with Internet addiction, and a control group of 30 healthy males with similar sociodemographic characteristics. A sociodemographic data form, Internet Addiction Test (IAT), Metacognitions Questionnaire (MCQ-30), Ruminative Response Scale-short version (RRS-SV), and Beck Depression Inventory (BDI) were used for data collection. Results: The MCQ-30 total, MCQ-30 uncontrollability and danger score, MCQ-30 need to control thoughts score and RRS-SV scores statistically significantly higher in study group compared the control group. After correcting for BDI by ANCOVA, the difference between MCQ-30 total score and RRS-SV disappeared. Conclusion: Internet addicts show ruminative responses instead of having an effective problem-solving attitude and defining problems; and this self-focused rumination leads an individual to recall more reinforced memories about the Internet so that the problem of Internet addiction becomes deeper. As a result of this study, although Internet addiction is accompanied by depression primarily or secondarily, manifestation of Internet addiction is exacerbated by depression through ruminative responses and metacognitions